Comparison Between First Line Target Therapy and Immunotherapy in Different Prognostic Categories of BRAF Mutant Metastatic Melanoma Patients: An Italian Melanoma Intergroup Study - Marconcini, Riccardo; Fava, Paolo; Nuzzo, Amedeo; Manacorda, Simona; Ferrari, Marco; De Rosa, Francesco; De Tursi, Michele; Tanda, Enrica Teresa; Consoli, Francesca; Minisini, Alessandro; Pimpinelli, Nicola; Morgese, Francesca; et al. (Frontiers in Oncology, 2022)
Background BRAF and MEK inhibitors target therapies (TT) and AntiPD1 immunotherapies (IT) are available first-line treatments for BRAF v600 mutant metastatic melanoma patients. ECOG PS (E), baseline LDH (L), and baseline number of metastatic sites (N) are well-known clinical prognostic markers that identify different prognostic categories of patients. Direct comparison between first-line TT and IT in different prognostic categories could help in first line treatment decision. Methods This is a retrospective analysis conducted in 14 Italian centers on about 454 metastatic melanoma patients, divided in 3 groups: group A—patients with E = 0, L within normal range, and N less than 3; group B—patients not included in group A or C; group C—patients with E > 0, L over the normal range, and N more than 3. For each prognostic group, we compared TT and IT in terms of progression free survival (PFS), overall survival (OS), and disease control rate (DCR). Results In group A, results in 140 TT and 36 IT-treated patients were, respectively, median PFS 35.5 vs 11.6 months (HR (95% CI) 1.949 (1.180–3.217) p value 0.009); median OS not reached vs 55 months (HR (95% CI) 1.195 (0.602–2.373) p value 0.610); DCR 99% vs 75% p value <0.001). In group B, results in 196 TT and 38 IT-treated patients were, respectively, median PFS 11.5 vs 5 months (HR 1.535 (1.036–2.275) p value 0.033); median OS 19 vs 20 months (HR 0.886 (0.546–1.437) p value 0.623); DCR 85% vs 47% p value <0.001). In group C, results in 41 TT and 3 IT-treated patients were, respectively, median PFS 6.4 vs 1.8 months (HR 4.860 (1.399–16) p value 0.013); median OS 9 vs 5 months (HR 3.443 (0.991–11.9) p value 0.052); DCR 66% vs 33% p value 0.612). Conclusions In good prognosis, group A—TT showed statistically significant better PFS than IT, also in a long-term period, suggesting that TT can be a good first line option for this patient category. It is only in group B that we observed a crossing of the survival curves after the 3rd year of observation in favor of IT. Few patients were enrolled in group C, so few conclusions can be made on it.